Investigation on pressure pulsation and modal behavior of the impeller in a nuclear reactor coolant pump. Issue 9 (8th May 2021) - Zhou, Qiang; Zhao, Xinwei; Pei, Lin; Li, Hongkun
Abstract: As the unique rotating component, the impeller is the core component of a nuclear reactor coolant pump (RCP), the dynamic properties of the impeller are critical for the safe operation of the whole reactor. The purpose of this study was to shed comprehensive light on the pressure pulsation and modal properties of a scaled RCP impeller via experimental and numerical methods. The numerical model was validated by an experiment connecting the pressure pulsation signals at the diffuser inlet, and a good agreement was obtained between the numerical and experimental results. Pressure pulsation acting on the impeller's blade is mainly dominated by the impeller rotating frequency, the vane passing frequency, and the double blade‐passing frequency, and the pressure pulsation acting on the blade's pressure surface is more intense than on the suction surface. The modal properties were obtained via the modal test and numerical methods with the impeller suspended as a free body in the air and submerged inside water. The reduction in the impeller natural frequencies was between 31.63% and 37.77% for the corresponding mode shape due to the added mass effect of the fluid. Based on the pressure pulsation characteristics acting on the impeller and the natural frequency of the impeller, it is considered there is no risk of resonance in the impeller. Finally, it is expected that the present work can provide scientific guidance to avoid hydraulic resonance in nuclear reactor coolant pumps. Abstract : The unsteady pressure pulsation characteristics and the modal behavior of a scaled reactor coolant pump impeller are investigated via experimental and numerical methods. The added mass effect of the surrounding water is analyzed, and the risk of impeller resonance is studied as well. ​